Effectiveness of Nondestructive Methods for the Evaluation of Structures Affected by Internal Swelling Reactions: A Review of Electric, Seismic and Acoustic Methods Based on Laboratory and Site Experiences. Issue 2 (30th January 2013) - Omikrine Metalssi, O.; Godart, B.; Toutlemonde, F.
Abstract : Internal swelling reactions (ISR) (which mainly comprise alkali‐silica reaction, alkali‐carbonate reaction, delayed ettringite formation, etc) are damage processes that affect the long‐term durability of concrete structures. The reactions are apparently characterized by series of closely spaced, tight map cracks with wide cracks appearing at regular intervals, and excessive tensile stresses in rebars. These phenomena are alarming for affected structure managers as they deal with people safety and structures operation. Moreover, there is no easily implemented way to stop the reactions. Prediction of concrete expansion, structural degradation, and assessment of efficiency and periodicity of repair works are crucial issues. The aim of this work is to explore the applicability of some nondestructive techniques (NDT) of investigations (electric, seismic, and acoustic methods) to differentiate the structure zones affected or not by the ISR for different exposure conditions. The collected experience highlights that the coupling between some of those nondestructive (ND) methods can reduce the measurement uncertainty and eliminates the factors that may influence the characterization of the structure parts affected by ISR. Nevertheless, for a complete structure reassessment, it is also desirable to refer to global geometrical/topographical survey and to destructive analysis methods on some cored samples for chemical analysis, petrography, and residual expansion measurements.